53.3k views
0 votes
2.сBOP-6-5-4-3-2-10В'Por boloAlA. (x.A. (x,y)+(-x,y+6)B. (x,y) → (x + 6,-y)(x,y) - (x - 12. y+6)D. (x,y)-(-x+6,-y)B.

User Vertex
by
4.7k points

1 Answer

1 vote

SOLUTION

For the image point A has the coordinates (-3, 6) and A' is (3, -6) so with a translation of


(x,\text{ y )}\rightarrow\text{ (}x+6,\text{ -y )}

We see A(-3, 6) as


A(-3,6)\rightarrow(-3+6,-6)\rightarrow A^(\prime)(3,-6)

And B(-2, 2) as


B(-2,2)\rightarrow(-2+6,-2)\rightarrow B^(\prime)(4,-2)

Therefore the correct translation is


(x,\text{ y )}\rightarrow\text{ (}x+6,\text{ -y )}

Option B is the correct answer.

User Gerardo Zinno
by
5.2k points